Representing Sylvia Plath - Bayley, Sally; Brain, Tracy (Cambridge University Press, 2011)
"Interest in Sylvia Plath continues to grow, as does the mythic status of her relationship with Ted Hughes, but Plath is a poet of enduring power in her own right. This book explores the many layers of her often unreliable and complex representations and the difficult relationship between the reader and her texts. The volume evaluates the historical, familial and cultural sources which Plath drew upon for material: from family photographs, letters and personal history to contemporary literary and cinematic holocaust texts. It examines Plath's creative processes: what she does with materials ranging from Romantic paintings to women's magazine fiction, how she transforms these in multiple drafts and the tools she uses to do this, including her use of colour. Finally the book investigates specific instances when Plath herself becomes the subject matter for other artists, writers, film makers and biographers"--